Ensaios em economia : evidências sobre economia da educação e sobre a corrupção no Brasil - Cardoso, Renata Pereira (2023)
This thesis aims to empirically analyze three social problems of public interest, the first two refer to education and the third to corruption in Brazil. For this purpose, three tests are pro-posed here. In the first test, we evaluated the factors associated with school dropout at differ-ent stages of education, under the hypothesis that boys and girls drop out for different reasons throughout their school career. Our results indicate that school dropout to work affects both boys and girls, being more intense for them and getting worse as the school years go by. For girls, in addition to work, marriage and children are also decisive factors for evasion, factors that are not very relevant for boys. In the second test, we empirically evaluated the effect of studying Youth and Adult Education (EJA) on the probability of passing the National Exami-nation for Certification of Youth and Adult Skills (Encceja). For certification at the Secondary Level, there was a lower probability of approval in Encceja for individuals taking EJA, in all subjects, with the negative effect being of greater magnitude for Languages and Writing, and Mathematics. For certification at Fundamental Level, worse performance was identified in the subjects of Languages and Writing, and Natural Sciences. In general, the results indicate low-er performance of the group participating in the EJA policy. Finally, in the third essay, we analyze corruption in Brazil, based on the estimation of a Microregional Corruption Index (IMRC), for 220 microregions in Brazil. Additionally, we evaluate spatial trends in estimated corruption. The results point to the formation of spatial clusters of corruption of the high-incidence type (high-high) for the regions of the Northern states, and low incidence (low-low) for those in the South. Finally, the work innovates by calculating an index objective with mi-cro-regional coverage. Furthermore, it indicates areas for State action in possible actions to combat corruption, as well as making available the IMRC, which enables various research on corruption.